2010
DOI: 10.5137/1019-5149.jtn.3246-10.2
|View full text |Cite
|
Sign up to set email alerts
|

Experience of carpal tunnel syndrome that operated using limited uni skin incision

Abstract: The limited uni skin incision is a safe and effective minimal invasive procedure for releasing the carpal tunnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Isik et al (2) reported that they achieved pain-numbing control and reduced scarring problems by applying microsurgical mini-incision proximal to the curvature of the distal flexion, which is finer than the skin, as in our study. Of the patients in our study, 86.4% reported complete/significant improvement in their complaints, while 88% were satisfied with the operation.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Isik et al (2) reported that they achieved pain-numbing control and reduced scarring problems by applying microsurgical mini-incision proximal to the curvature of the distal flexion, which is finer than the skin, as in our study. Of the patients in our study, 86.4% reported complete/significant improvement in their complaints, while 88% were satisfied with the operation.…”
Section: Discussionmentioning
confidence: 51%
“…The recurrent thenar branch of the median nerve is also at risk for possible anatomical variations. In addition, palmar arteries, especially the superficial palmar arc, may be injured (2,9). No damage to these structures occurred in any of the patients in our study.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This traditional approach also carries the risk of pillar pain and painful hypertrophic scar formation. These risks led us to explore different types of the incision with which to perform the open surgery (Figure 4A–4D) [15,17,18,20]. For example, a small palmar incision has been used to overcome these complications (Figure 4D) [11,20], and its use achieved good clinical results, but the risk of injury to the MN cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%